Multiple Choice Questions in Biochemistry - Gupta RC; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2004)
This book Multiple Choice Questions in Biochemistry has been written to provide a comprehensive question bank to students covering nearly the entire syllabus in Biochemistry. Multiple choice questions (MCQs) constitute an important method for objective assessment of an examinee$1 (Bs knowledge. In this book includes 2,100 MCQs organised into 27 chapters covering core topics in Biochemistry as well as the emerging areas. Each chapter has been reviewed by an experienced teacher. Referenced answers have been provided to all the questions. Most of the questions are based on Harper$1 (Bs Biochemistry, 25th edition. Coverage of the subject in this book is exhaustive and balanced. While topics like vitamins, minerals, diet and nutrition, still important in developing countries, find adequate coverage, rapidly advancing areas like recombinant DNA technology, immunochemistry and cancer have not been ignored. Error-free edition of this book, a number of questions have been replaced or substantially revised. About 300 new questions have been added. A new chapter on metabolism of xenobiotics has also been added. The book will help students in quick revision of the subject as well as in preparing for undergraduate examinations and pre-PG entrance examinations.s
Keywords: Biochemistry,MCQs and Self-assessment; Electronic books